Variability of the female genital system morphology and of sperm storage in terrestrial isopods (Isopoda, Oniscidea) - Longo, G; Trovato, M; Mazzei, V (The Italian journal of zoology, 2011)
In females of Isopoda Oniscidea, the genital system displays a remarkable variability of its morphological and functional organization as possible adaptation to different strategies of sperm storage. In all the oniscidean species, the sperm received from the male during mating are temporarily stored in the bursa copulatrix, a chitinous pouch of the oviduct. In 27 of the 32 species we studied, the sperm that remain in the bursa copulatrix after the fertilization of eggs of the first oviposition are transferred into the seminal receptacle, where they can be stored for a variable time. In these species, the seminal receptacle is a small kidney-shaped cup, localized at the insertion of the oviduct into the ovary. Only in two species of the genus Trichoniscus, in which the oviduct is very short, is the bursa copulatrix modified to form a large lateral diverticle.Instead, in three species of the family Halophilosciidae, Halophiloscia couchii, Halophiloscia hirsuta and Stenophiloscia glarearum, the ovary is consistently shorter, while the seminal receptacle is greater; after mating, both seminal receptacle and ovary appear completely filled with sperm. Finally, in two species of the family Tylidae, Tylos europaeus and Helleria brevicornis, the female genital system lacks specialized structures for sperm storage, and every oviposition requires a mating for the eggs fertilization.The authors present some hypotheses to explain the variability of the female genital system morphology and the sperm storage strategies.